Child Right For The Physical Body In Jodi Picoult's Novel My Sister's Keeper (2004): A Sociological Approach - Larasaty, Niken; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
This study is about child right for the physical body in My Sister's Keeper novel. The problem of this study is Anna Fitzgerald prosecutes her mother to stop being donor for her sister. Anna asks a lawyer to make a petition for her mother. Anna wants medical emancipation for her body. This reserach paper belongs to qualitative research. The method to analyze of this data is descriptive analysis. The novel is analyzed using the structural elements of the novel. Types of data sources that are used in this research are primary data source and secondary data source. The primary data source is My Sister's Keeper novel. The secondary data sources related to the study, such as website and some books that support this analysis. The method of collecting data in this research is taking notes. The research method to analyze the novel is based on sociological approach proposed by Laurenson and Swingewood. The result of this study shows the following conclusions, if the novel is suitable with the social condition in America. There is a relation between the novel with the social condition in reality. Child right for the physical body must be guaranteed and protected by parents, society, goverment and the state. Everyone has the right for their own body. No organ shall be removed from the body and nobody can preassure to donate the organ.